Mental health challenges and perceptions of stigma among youth living with HIV in Tanzania. - Laura S Mkumba; Fortunata Nasuwa; Blandina T Mmbaga; Aisa M Shayo; Coleen K Cunningham; Karen E O'Donnell; Dorothy E Dow (PLoS ONE)
Youth living with HIV (YLWH) face psychosocial challenges and HIV-related stigma, which impact adherence to antiretroviral therapy (ART). This study was designed to understand better the change in mental health symptoms and experiences with stigma among YLWH in Tanzania who completed the original pilot Sauti ya Vijana (SYV), a mental health and life skills group intervention. YLWH who completed SYV and demonstrated a change of ≥2 points in either direction on their Patient Health Questionnaire PHQ-9 (depression screener) from baseline to 18 months were purposively sampled. HIV Stigma was measured using 10-questions from the Berger HIV Stigma Scale, and findings ranged from 4-16 for internal stigma and 6-24 for external stigma. In-depth interviews (IDI) were conducted in Kiswahili and included topics such as history of mental health challenges, perceptions of stigma, and experiences with the SYV intervention. Interviews were transcribed, translated to English, and analyzed for emergent themes. Ten youth, 18-25 years of age, were interviewed; 70% were male. Mean (SD) PHQ-9 scores were 7.3 (SD = 3.5) at baseline and 5.6 (SD = 5.0) at 18 months. All participants reported experiencing intermittent episodes of mental health challenges due to difficult interpersonal relationships and fear of stigma. Youth relied on peer support and skills from the SYV intervention to cope with mental health challenges and stigma. Participants reported fear of being stigmatized by others, which led to behaviors such as skipping medication or avoiding situations for worry about unintentional disclosure. All participants endorsed experiencing external stigma on the HIV stigma scale; however, only 3 of 10 participants reported experiencing enacted stigma when directly asked to describe an experience during in-depth interviews. Participants described how SYV helped them have "more confidence", accept themselves, and incorporate positive coping skills such as relaxation (deep breathing) when they felt stressed. The findings suggest SYV helped YLWH accept themselves, develop positive coping methods, and identify and form peer social support; but stigma remains common. Descriptions of stigma were not recognized as such; experiences of enacted stigma were acknowledged by some participants. More research is needed to understand and measure mental distress and wellness as well as stigma in this population so that interventions may more accurately detect change in key outcomes.